Consumer Protection in India (With Special Reference to Andhra Pradesh) - Praveen, S. (Prabandhan: Indian Journal of Management, 2009)
Our country is a developing country facing problems like illiteracy, poverty and unemployment; the self-motivated manufacturers and traders can exploit people very easily. They are exploiting the consumers because of their ignorance of their consumer rights. Though they are aware of their consumer rights, they are unable to get justice through the courts, which are known for their delay, very completive nature of rules and regulations and expansiveness. In these circumstances, the consumer protection has acquired immense importance. The purpose of the study is to analyze the role played/playing by the consumer protection agencies and to suggest measures.